Human megakaryocytes confer tissue factor to a subset of shed platelets to stimulate thrombin generation - Brambilla, Marta; Facchinetti, Laura; Canzano, Paola; Rossetti, Laura; Ferri, Nicola; Balduini, Alessandra; Abbonante, Vittorio; Boselli, Daniela; De Marco, Luigi; Di Minno, Matteo N.D.; Toschi, Vincenzo; Corsini, Alberto; Tremoli, Elena; Camera, Marina (Thrombosis and Haemostasis, 2015)
Tissue factor (TF), the main activator of the blood coagulation cascade, has been shown to be expressed by platelets. Despite the evidence that both megakaryocytes and platelets express TF mRNA, and that platelets can make de novo protein synthesis, the main mechanism thought to be responsible for the presence of TF within platelets is through the uptake of TF positive microparticles. In this study we assessed 1) whether human megakaryocytes synthesise TF and transfer it to platelets and 2) the contribution of platelet-TF to the platelet hemostatic capacity. In order to avoid the cross-talk with circulating microparticles, we took advantage from an in vitro cultured megakaryoblastic cell line (Meg-01) able to differentiate into megakaryocytes releasing platelet-like particles. We show that functionally active TF is expressed in human megakaryoblasts, increased in megakaryocytes, and is transferred to a subset of shed platelets where it contributes to clot formation. These data were all confirmed in human CD34pos- derived megakaryocytes and in their released platelets. The effect of TF silencing in Meg-megakaryoblasts resulted in a significant reduction of TF expression in these cells and also in Meg-megakaryocytes and Meg-platelets. Moreover, the contribution of platelet-TF to the platelet hemostatic capacity was highlighted by the significant delay in the kinetic of thrombin formation observed in platelets released by TF-silenced megakaryocytes. These findings provide evidences that TF is an endogenously synthesised protein that characterises megakaryocyte maturation and that it is transferred to a subset of newly-released platelets where it is functionally active and able to trigger thrombin generation.
Keywords: Megakaryocytes; platelets; tissue factor; thrombin generation